Mechanical and Microstructural Evaluation of Ca,Sr-Stabilized Zirconia/Metakaolin Geopolymer Composites for Dental Biomaterial Applications - Bo-Kwan Kong; Riaid Alsaeedi; Z. Ozdemir (Tinta Emas Publisher, 2026)
This study investigated the mechanical and microstructural characteristics of Ca,Sr-stabilized zirconia nanoparticles incorporated into a metakaolin-based geopolymer as a dental biomaterial candidate. Zirconium(IV) chloride, calcium chloride, and strontium chloride hexahydrate were processed through a chitosan-assisted sol–gel route, calcined at 900 °C, ultrasonically dispersed in ethanol, and combined with metakaolin at zirconia/metakaolin mass ratios of 80:20 (N80M20), 70:30 (N70M30), and 60:40 (N60M40). Fifteen specimens were prepared, with five specimens in each formulation. The synthesized powder was characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM), whereas the composites were evaluated by Vickers microhardness, three-point flexural testing, and SEM. The XRD pattern indicated a stabilized high-symmetry zirconia phase corresponding to ICDD/JCPDS card 79-1796, and SEM showed nanoscale particles of approximately 53–60 nm with rounded morphology. The microhardness increased with increasing metakaolin content and reached 118.76 HV in N60M40. Conversely, N80M20 exhibited the highest mean flexural strength, followed by N70M30 and N60M40. One-way ANOVA showed that the differences in flexural strength were not statistically significant (F = 0.548, p > 0.05). The mechanical trends were consistent with the observed microstructural differences: N80M20 contained microcracks, N70M30 displayed micropores and particle agglomeration, and N60M40 formed a more continuous and textured matrix. The results demonstrate that the balance between zirconia-particle packing and geopolymer-matrix formation governs the mechanical response of the composites. N60M40 provided the highest surface hardness, whereas N80M20 retained the highest flexural response.